ANALISIS KANDUNGAN LOGAM BERAT Pb, Cu, Cd, Cr PADA TANAMAN PADI DAN JAGUNG YANG SISTEM PENGAIRANNYA BERASAL DARI SUNGAI BADUNG - Widyasari, Ni Luh; Rai, I Nyoman; Sila Dharma, IGB; Sudiana Mahendra, Made (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2023)
This research aims at identifying the content of heavy metals, namely Pb, Cu, Cd, and Cr in the rice and corn cultivated on the agricultural land of Subak Kerdung, Pemogan Village, South Denpasar District. Rice and corn plants are suspected of having indications of heavy metals due to pollution of the downstream Badung River, which is used as irrigation in Subak Kerdung agricultural land. The analysis of heavy metal contents is conducted on the rice and corn plant organs samples, including roots, stems, leaves, and seeds. The test results show that the organs of rice and corn plants detect the contents of heavy metals Pb, Cu, Cd, and Cr which exceed quality standards. According to the results of analysis tests on organs of the rice plant, the content of heavy metal Pb is detected 21.95 mg/kg; heavy metal Cu 170.42 mg/kg; heavy metals Cd 0.35 mg/kg; and heavy metal Cr 7.03 mg/kg. Meanwhile, the results of analysis test on organs of the corn plant detect the content of heavy metal Pb 16.96 mg/kg; heavy metal Cu 58.16 mg/kg; heavy metal Cd 2.5 mg/kg; and heavy metal Cr 3.16 mg/kg. Therefore, it can be concluded that the content of heavy metals Pb, Cu, Cd, and Cr is more detected in the roots of rice and corn plants, also partially translocated to their stems, leaves, and seeds. Keywords: heavy metals; rice plants; corn plants; Badung rivers